2019
DOI: 10.1101/520544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role for gene-environment interactions in Autism Spectrum Disorder is suggested by variants in genes regulating exposure to environmental factors

Abstract: Introduction: Autism Spectrum Disorder (ASD) is a clinically heterogeneous neurodevelopmental disorder defined by deficits in social communication and interaction and repetitive and stereotyped interests and behaviors. ASD heritability estimates of 50-83% support a strong role of genetics in its onset, with large sequencing studies reporting a high burden of rare potentially pathogenic copy number variants (CNVs) and single nucleotide variants (SNVs) in affected subjects. Recent data strongly suggests that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 122 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…Copy number variations were identified in chromosome 19 for multiple genes including LGALS16 in association with clinical features, such as histological type, ethnicity, disease stage, and familial history, of breast cancer using tumor samples from a Brazilian cohort [ 63 ]. In addition, LGALS16 was determined to be a moderate impact variant associated with autism spectrum disorder, consisting of a missense single nucleotide variant (SNV), which was reported as detrimental by bioinformatic tools SIFT and PolyPhen-2 [ 64 ]. LGALS16 also had greater SNVs within the 3′ flank region with one or more mutations in patients with diffuse large B-cell lymphoma [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Copy number variations were identified in chromosome 19 for multiple genes including LGALS16 in association with clinical features, such as histological type, ethnicity, disease stage, and familial history, of breast cancer using tumor samples from a Brazilian cohort [ 63 ]. In addition, LGALS16 was determined to be a moderate impact variant associated with autism spectrum disorder, consisting of a missense single nucleotide variant (SNV), which was reported as detrimental by bioinformatic tools SIFT and PolyPhen-2 [ 64 ]. LGALS16 also had greater SNVs within the 3′ flank region with one or more mutations in patients with diffuse large B-cell lymphoma [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Public databases such as the Comparative Toxicogenomic Database (CTD) ( Davis et al, 2021 ), Gene Expression Omnibus (GEO) ( Clough and Barrett, 2016 ), Simons Simplex Collection (SSC) ( Fischbach and Lord, 2010 ), and Autism Sequencing Consortium (ASC) ( Buxbaum et al, 2012 ) can be used to discover novel interactions between chemicals and genes associated with DDs. For example, an integrative analysis using CTD, SSC, and ASC revealed a total of 212 gene–environment interaction pairs putatively relevant for ASD, and provided a list of candidate genes susceptible to chemicals associated with ASD, such as valproic acid, benzo(a)pyrene, bisphenol A, particulate matter, and perfluorooctane sulfonic acid ( Santos et al, 2019 ). A novel in silico approach using GEO identified tumor suppressors: p53, retinoblastoma 1, and Kr ü ppel-like factor 8 as leading nodes in the network of developmental neurotoxicity of selective serotonin reuptake inhibitors and antidepressants associated with ASD ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, more than one thousand autism genes have been investigated. Using the SFARI gene platform, approximately 212 genes (environment interacting genes) have been studied [ 37 , 38 ]. More recently, studies reported that dysregulated gene expression is associated with inflammatory cytokines and behavioural severity in ASD [ 39 , 40 ].…”
Section: Body Of the Papermentioning
confidence: 99%